2004
DOI: 10.1111/j.1537-2995.2004.04073.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hepatitis C virus infection among blood donors in northern Thailand

Abstract: Our data indicate that illicit IDU and a history of transfusion are important risk factors for HCV infection in Thailand. Also, our data suggest there may be some risk of transmission by sex or other close contact between spouses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
50
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 31 publications
2
50
0
Order By: Relevance
“…Some studies have been conducted recently on the worldwide population. (18,19) For example, a study to determine the epidemiology of HCV in 2014 showed that the prevalence of HCV-Ab is 2% for adults and 1.6% for all ages all over the world. The prevalence of viremia is 1.4% in adults and 1.1% in all ages.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have been conducted recently on the worldwide population. (18,19) For example, a study to determine the epidemiology of HCV in 2014 showed that the prevalence of HCV-Ab is 2% for adults and 1.6% for all ages all over the world. The prevalence of viremia is 1.4% in adults and 1.1% in all ages.…”
Section: Discussionmentioning
confidence: 99%
“…HCV genotype 6 viruses mainly circulate in South East Asia (SEA), including Vietnam (Tokita et al, 1994), Indonesia (Tokita et al, 1996), Thailand (Chinchai et al, 2003;Thaikruea et al, 2004), Cambodia (Caruana et al, 2005) and Myanmar (Shinji et al, 2004). Currently, genotype 6 viruses are classified into 17 subtypes (6a-6q) based on complete genome analysis (Lu et al, 2006(Lu et al, , 2007aTokita et al, 1996Tokita et al, , 1998.…”
mentioning
confidence: 99%
“…Examples supporting this are that among four commercial blood donors from Hanoi (VN004, VN085, VN235, and VN405) found to be infected with HCV, three individual subtypes (6d, 6k, and 6h) were discovered [Tokita et al, 1994]. In addition, among 26 blood donors positive for HCV genotype 6 from Chiang Mai, Thailand, a total of six subtypes (6b, 6f, 6i, 6j, 6m, and 6n) was identified [Thaikruea et al, 2004].…”
Section: Discussionmentioning
confidence: 87%
“…However, except for seven subtypes (6a, 6b, 6d, 6g, 6h, 6k, and 6n), the other ten subtypes still lack the complete genomic sequences [Simmonds et al, 2005;Lu et al, 2006]. Epidemiologically, genotype 6 variants were exclusively identified in Southeastern Asia or immigrants from this geographic region [Mellor et al, 1995Stuyver et al, 1995;Bernier et al, 1996;Doi et al, 1996;Theamboonlers et al, 2002;Shinji et al, 2004;Thaikruea et al, 2004;Apichartpiyakul et al, 1994]. In one of our recent studies, two related variants, HK6554 and GX004, were also discovered in samples from Hong Kong and the Guangxi province in southern China from patients with injection drug use and coinfection with HIV-1.…”
Section: Introductionmentioning
confidence: 92%